2021
DOI: 10.1002/ijgo.13880
|View full text |Cite
|
Sign up to set email alerts
|

FIGO staging for carcinoma of the vulva: 2021 revision

Abstract: To revise the FIGO staging for carcinoma of the vulva using a new approach that involves analyses of prospectively collected data. The FIGO Committee for Gynecologic Oncology reviewed the recent literature to gain an insight into the impact of the 2009 vulvar cancer staging revision. The Committee resolved to revise the staging with a goal of simplification and actively collaborated with the United States National Cancer Database to analyze prospectively collected data on carcinoma of the vulva. Many tumor cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 15 publications
(32 reference statements)
0
53
0
Order By: Relevance
“…As a result, the Committee decided to update the staging for vulvar cancer. 39 NCDB vulvar cancer data collected over 7 years (2010–2017) was utilized in defining the new FIGO vulvar cancer staging (Table 2 ). This new staging is applicable to most malignancies arising from the vulva, except melanoma.…”
Section: Management Of Vulvar Cancermentioning
confidence: 99%
“…As a result, the Committee decided to update the staging for vulvar cancer. 39 NCDB vulvar cancer data collected over 7 years (2010–2017) was utilized in defining the new FIGO vulvar cancer staging (Table 2 ). This new staging is applicable to most malignancies arising from the vulva, except melanoma.…”
Section: Management Of Vulvar Cancermentioning
confidence: 99%
“…The International Federation for Gynaecology and Obstetrics (FIGO) staging system for vulvar cancer has recently been updated (see Table 1 ) [ 4 ]. The term “Advanced Vulvar Cancer” may be considered to include very large or locally advanced tumours (stage I and II with tumours >4 cm in diameter); those with macroscopic nodal metastases (stage IIIB and IIIC); those that involve the urethra, bladder, anorectum, or pelvic bone (stage IVA); those for which adequate surgical excision requires sacrifice of the urethra or anus or an exenterative procedure; and those with distant metastases (stage IVB).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis comprising 5015 cases of vulvar cancer and 2764 cases of VIN revealed that the prevalence of HPV in vulvar cancer was 39.7% and 76.3% in VIN lesions [226]. Basaloid and warty variants of VSCC are more common in younger women, are often associated with HPV DNA detection [227], and get similar risk factors as in cervical cancer. HPV prevalence in invasive basaloid and warty tumors is more frequent (69.4%) than in invasive VSCC types observed in elderly women (13.2%) [215].…”
Section: Vulvar Cancermentioning
confidence: 99%
“…Infection with HR-HPVs and viral DNA integration into the host cell genome seems to be related to the progression of VIN and its key steps are similar to those described in cervical cancer [229]. Recently, it has been recommended to document the HPV status of vulvar carcinomas (HPV-associated or HPV-independent) [227]. This is assessed by p16 block-type immunoreactivity and/or positive molecular testing for HPV.…”
Section: Vulvar Cancermentioning
confidence: 99%